2008
DOI: 10.1016/j.jcf.2007.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis transmembrane conductance regulator (CFTR) gene 5T allele may protect against prostate cancer: A case-control study in Chinese Han population

Abstract: Our results indicate that the low expression CFTR polymorphisms may contribute to a reduced risk of prostate cancer in Chinese Han population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The present study has investigated the possible mechanism underlying this pH change and demonstrated for the first time the involvement of CFTR in mediating prostatic HCO 3 − secretion, which may be enhanced upon bacterial infection or inflammation. Apart from demonstrating CFTR expression in rat prostatic epithelium, which is consistent with that previously found in human prostate [33], [34], [35], we have also elucidated the functional roles of CFTR in the prostate in health and disease. By measuring the rate of pHi recovery from cellular alkalization, in the presence or absence of extracellular Cl − in conjunction with the use of the cAMP agonist and CFTR inhibitor, we have demonstrated that prostatic epithelium can extrude HCO 3 − under unstimulated condition through a Cl − /HCO 3 − exchanger since removal of extracellular Cl − greatly attenuated the pHi recovery rate.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The present study has investigated the possible mechanism underlying this pH change and demonstrated for the first time the involvement of CFTR in mediating prostatic HCO 3 − secretion, which may be enhanced upon bacterial infection or inflammation. Apart from demonstrating CFTR expression in rat prostatic epithelium, which is consistent with that previously found in human prostate [33], [34], [35], we have also elucidated the functional roles of CFTR in the prostate in health and disease. By measuring the rate of pHi recovery from cellular alkalization, in the presence or absence of extracellular Cl − in conjunction with the use of the cAMP agonist and CFTR inhibitor, we have demonstrated that prostatic epithelium can extrude HCO 3 − under unstimulated condition through a Cl − /HCO 3 − exchanger since removal of extracellular Cl − greatly attenuated the pHi recovery rate.…”
Section: Discussionsupporting
confidence: 87%
“…In fact, our previous studies have demonstrated the involvement of CFTR in mediating uterine and oviductal HCO 3 − secretion, which are vital to the fertilizing capacity of sperm and embryo development [30], [31], [32]. Since CFTR is also known to be expressed in the human prostate [33], [34], [35], it may also play a role in prostatic HCO 3 − secretion as well although the physiological role of CFTR in the prostate has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Blockage of these channels can suppress the growth and proliferation of human prostate cancer cells [30, 31]. A dysfunctional CFTR may weaken the ability of cancer cells to survive by handling proliferative homeostasis and thereby strengthening their pro-apoptotic potential [9, 31]. On the other hand, it has been shown that a dysfunctional CFTR was responsible for elevated blood ATP concentrations in mice and in CF patients [8, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who were CFTR mutation carriers were found to be at an increased risk for young onset of pancreatic cancer [5]. An inverse association between CF gene mutations and incidence of several cancers, such as melanoma[3, 6], breast cancer[68], colon cancer[6] and prostate cancer[9], was also reported. However, no studies have been reported on the association between CFTR and lung cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the best BPSO-generated SNP barcodes listed are more protective when more SNPs are selected. Similarly, accumulating evidence showed that some SNPs were reported to protective against many types of cancers [26][27][28][29]. For example, the rs243865 (C-1306T of MMP2 gene) was found to be associated with substantial reduction in risk of breast cancer [26] although they were not focused on the SNP-SNP interactions like our study.…”
Section: The Ranks Of the Odds Ratios Indicate Lowest Risk Group For mentioning
confidence: 45%